Analyzing bone, blood vessels, and biomaterials with microcomputed tomography. - Guldberg, R.E.
Quantitative tools such as micro-CT are needed for tissue engineering to evolve beyond a qualitative, observational field and accelerate the clinical realization of regenerative technologies. As faster, higher-resolution micro-CT systems become available for both in vitro and in vivo studies and the development of improved contrast agents allows micro-CT imaging to be extended to nonmineralized tissues, additional novel applications related to tissue engineering are sure to emerge.
Keywords: Biomaterials; Blood vessels; Bone; Micro-CT.; Microcomputed tomography; Regenerative technologies; Tissue engineering